Complete assessment of whole-body n-3 and n-6 PUFA synthesis-secretion kinetics and DHA turnover in a rodent model - Adam H. Metherel; R. J. Scott Lacombe; Raphaël Chouinard-Watkins; Kathryn E. Hopperton; Richard P. Bazinet (Journal of Lipid Research, 2018)
Previous assessments of the PUFA biosynthesis pathway have focused on DHA and arachidonic acid synthesis. Here, we determined whole-body synthesis-secretion kinetics for all downstream products of PUFA metabolism, including direct measurements of DHA and n-6 docosapentaenoic acid (DPAn-6, 22:5n-6) turnover, and compared n-6 and n-3 homolog kinetics. We infused labeled α-linolenic acid (ALA, 18:3n-3), linoleic acid (LNA, 18:2n-6), DHA, and DPAn-6 as 2H5-ALA, 13C18-LNA, 13C22-DHA, and 13C22-DPAn-6. Eight 11-week-old Long Evans rats fed a 10% fat diet were infused with the labeled PUFAs over 3 h, and plasma enrichment of labeled products was measured every 30 min. The DHA synthesis-secretion rate (94 ± 34 nmol/day) did not differ from other PUFA products (range, 21.8 ± 4.3 nmol/day to 408 ± 116 nmol/day). Synthesis-secretion rates of n-6 and n-3 PUFA homologs were similar, except 22:4n-6 and DPAn-6 had lower synthesis rates. However, daily turnover from newly synthesized DHA (0.067 ± 0.023%) was 56-fold to 556-fold slower than all other PUFA turnover and was 130-fold slower than that determined directly from the total plasma unesterified DHA pool. In conclusion, n-6 and n-3 PUFA synthesis-secretion kinetics suggest that differences in turnover, not in synthesis-secretion rates, primarily determine PUFA plasma levels.